Introducing Agroecology - Zachary Brym; Hamutahl Cohen; Hannah Wooten; Emma Matcham; David Outerbridge (EDIS)
This document aims to introduce the foundational ideas and main concepts of agroecology to a general audience with some specific examples for implementing agroecology on farms and gardens in commercial, hobby, and educational contexts. Written by Zachary Brym, Hamutahl Cohen, Hannah Wooten, Emma Matcham, and David Outerbridge, and published by the UF/IFAS Agronomy Department, June 2023.